IMPLEMENTASI KEBIJAKAN BANTUAN PANGAN NON-TUNAI (BPNT) DI DESA RANTAU JAYA UDIK KECAMATAN SUKADANA KABUPATEN LAMPUNG TIMUR - Rakhmadani, Syeni; Wardhana, Yuditya; Gusnita, Ari (Jurnal Ilmiah Dinamika Sosial, 2022)
Since now, the handling of poverty in Indonesia is still being pursued with various strategies for handling it. One of them is the issuance of the Non-Cash Food Assistance (BPNT) policy which is based on the Presidential Regulation of the Republic of Indonesia Number 63 of 2017 concerning the Distribution of Non-Cash Aid. However, in its implementation, there are still many problems such as recipients of aid who are not on target, such as the case that occurred in Rantau Jaya Udik Village, Sukadana District. From a total of 221 Beneficiary Families (KPM), there are 39 data that are not on target. The purpose of this study was to analyze how the implementation of BPNT distribution in Rantau Jaya Udik Village, Sukadana District, East Lampung Regency. This study uses a descriptive method with a qualitative approach. The results of this study indicate that the implementation of BPNT distribution in Rantau Jaya Udik Village has not run well, this can be seen from the characteristics of the problem, it can be seen that there are invalid beneficiary data obtained from the Integrated Data on Social Welfare of the Ministry of Social Affairs of the Republic of Indonesia, namely 39 Beneficiary Families. In implementing this policy, the contents of this policy are clearly contained in the Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 20 of 2019 concerning the Distribution of Non-Cash Food Aid and support from the implementers and the community for this program. In terms of the environment, social, community economy and the level of technological progress of the community, it is quite low as seen from many KPMs who still do not understand in using the Prosperous Family Card.